Developmental validation of the ANDE™ rapid DNA system with FlexPlex™ assay for arrestee and reference buccal swab processing and database searching. (May 2019) - Carney, Christopher; Whitney, Scott; Vaidyanathan, Janaki; Persick, Rebekah; Noel, Fabrice; Vallone, Peter M.; Romsos, Erica L.; Tan, Eugene; Grover, Ranjana; Turingan, Rosemary S.; French, Julie L.; Selden, Richard F.
Highlights: ANDE 6C uses 6-dye, 27-locus STR assay and integrated Expert System for reference buccal swabs without human intervention. Automated processing and data interpretation allow the system to be operable in the field. System was validated on 2045 samples from 1387 individuals on 13 instruments run by 6 different laboratories. 99.99% concordant alleles and 92% first pass success rate meet NDIS approval requirement of the U.S. Rapid DNA Act of 2017. Abstract: A developmental validation was performed to demonstrate reliability, reproducibility and robustness of the ANDE System with the FlexPlex assay, including an integrated Expert System, across a number of laboratories and buccal sample variations. Previously, the related DNAscan™/ANDE 4C Rapid DNA System using the PowerPlex ® 16 assay and integrated Expert System Software received NDIS approval in March 2016. The enhanced ANDE instrument, referred to as ANDE 6C, and the accompanying 6-dye, 27-locus STR assay, referred to as FlexPlex, have been developed to be compatible with all widely used global loci, including the expanded set of the CODIS core 20 loci. Six forensic and research laboratories participated in the FlexPlex Rapid DNA developmental validation experiments, testing a total of 2045 swabs, including those obtained from 1387 unique individuals. The goal of this extensive and comprehensive validation was to thoroughly evaluate and document the ANDE System and its internal Expert System to reliably genotype reference buccal swab samples in a manner compliant with the FBI's Quality Assurance Standards and the NDIS Operational Procedures. The ANDE System, including automated Expert System analysis, generated reproducible and concordant results for buccal swabs when testing various instruments at different laboratories by a number of different operators. When testing a number of non-human DNAs, including oral bacteria, the ANDE System and FlexPlex assay demonstrated limited cross-reactivity. Potential PCR inhibitors were evaluated as part of the validation and no inhibition was detected. Reproducible and concordant profiles were generated from buccal swab samples collected with a limit of detection appropriate for buccal swab collections from arrestees. The precision and resolution of the System met industry standards for detection of microvariants and single base resolution. The integrated Expert System appropriately demonstrated the ability to correctly pass or fail profiles for CODIS upload without human review. During this comprehensive developmental validation, the ANDE System successfully interpreted over 2000 samples tested with over 99.99% concordant alleles. The data package described herein led to the ANDE System with the FlexPlex assay receiving NDIS approval in June 2018.